The Impact of the Implementation of the Cash Social Assistance Program in the Kiniar Sub District Minahasa Regency - Kusen, Stefani Natalia; Masengi, Evi Elvira; Mandagi, Marthinus (Technium Social Sciences Journal, 2023)
The state has an obligation to overcome the problem of poverty in order to help and protect all of its people so they can live a decent life, especially due to COVID-19. One of the policies of the Indonesian government is Cash Social Assistance. The purpose of this study is to 1) analyze and describe how the policy implementation of the Cash Social Assistance program in the Kiniar Sub District; 2) Knowing the impact on the community in the implementation of the Social Cash Assistance program in the Kiniar Sub District, Minahasa Regency. This study used qualitative research methods. The research location is the Kiniar sub-district, Minahasa Regency. Researchers used purposive sampling with data collection techniques in the form of interviews, observation and documentation. Data analysis techniques are data reduction, data presentation, and concluding. The study results show that 1) the implementation of the distribution of funds for Cash Social Assistance participants in the Kiniar Sub District is right on target. Participants who receive assistance can take assistance directly at the distribution post, namely PT. POS Indonesia in the city of Tondano; 2) The Cash Social Assistance Program has positive and negative impacts on beneficiary communities. The positive impact is that this assistance can help beneficiary communities in their daily lives, while the negative impact is that this program creates a culture of dependency and laziness.